The role of vaccines in combating antimicrobial resistance. (30th September 2020) - Jit, M; Cooper, B
Abstract: Vaccination is one of the most effective measures to reduce antimicrobial resistance in both human and animal pathogens. This presentation reviews the multiple pathways by which vaccines may act to reduce resistance: they can prevent infections by focal pathogens, reducing the need to use antibiotics; they can selectively protect against resistant subtypes of a pathogen; they can reduce infections by other pathogen species which are routinely treated with antibiotics (not necessarily appropriately) thus reducing bystander selection; and they could selectively reduce transmission in settings such as hospitals which may have higher proportions of resistant strains. Because vaccines are highly specific to their targeted pathogens, they are much less likely to induce resistance compared to antibiotics. Hence, they can be delivered to large populations as a preventive measure to reduce transmission. The impact of vaccination on resistance has been demonstrated for vaccines against Streptococcus pneumoniae, Haemophilus influenzae type b and influenza. Current and pipeline vaccines against pathogens such as Vibrio cholerae, Escherichia coli, Salmonella typhi, RSV, diarrhoeal viruses and nosocomial bacteria may also have potential to reduce resistance. Economic evaluations of vaccines need to be expanded to capture their benefits in reducing resistance, in order to incentivize development and introduction of the right vaccines. Accurately doing so will require health systems, epidemiological and economic research.